What do people say about a reality show? Analysis of Spanish Big Brother’s Facebook comments (2011-2019) - Cabeza, José (2023)
This article analyses the complete history of the Facebook forum on Big Brother Spain during 2011-2019. For this study, more than 1.2 million Facebook comments were retrieved, and later thematic patterns from these units of content were identified and analysed. It examines what the most recurrent issues the fans talk about, and their standpoint on those. Forum participants accept and fully participate in the logic of the program (both its mechanics and its end goal), but sometimes mistrust and question the broadcaster’s impartiality when they consider that the network is meddling in the reality for commercial purposes. Yet any censorship made by the program on events which may hurt its image goes unnoticed. Viewers, largely women, criticize female contestants three times (2.79) more than men. However, there is also a degree of gender alliance between forum members and female contestants, as these receive more support to win the contest.